Little women - Alcott, Louisa May, 1832-1888 (Penguin classics., 1989)
The classic story of the March family whose 4 daughters are growing up in New England in the mid-1800s. There are numerous sequels, for example, 'Little Men' and 'Jo's Boys'. Annotation. 'Little Women' is the heartwarming story of the March family that has thrilled generations of readers. It is the story of four sisters -- Jo, Meg, Amy and Beth -- and of the courage, humor and ingenuity they display to survive poverty and the absence of their father during the Civil War.